STRATEGY FOR ENVIRONMENTALLY SUSTAINABLE TRANSPORT (American Journal of Research in Humanities and Social Sciences, 2023)
It is known that today one of the most important features of modern transport policy is the requirement for transport to comply with the goals of sustainable development; the need to reduce its negative impact on the environment and public health is important on a global scale. These aspects are discussed in detail in this article.